Impact of Ondancentron In Intra-Anesthesia During Caesarean Section: A Meta-Analysis of Randomized Trials - Susanti, Indah; Mixrova Sebayang, Septian; Burhan, Asmat (Global Indonesia Health Care (GOICARE), 2024)
Background: The medulla distinguishes nausea and vomiting. Intra-operative nausea and vomiting (IONV) can occur up to 80% of the time following spinal anesthesia for caesarean delivery. Patients are uncomfortable and surgery is halted. Aims: This meta-analysis examines the effects of ondancentron on IONV, hypertension, and pruritus. Methods: The databases examined were CINAHL, PubMed, ScienceDirect, Wiley, and Scopus, with coverage from September 2014 to July 2024. Article text must be complete with Uji Coba Terkendali Acak design and published in English. They used R-Studio 4.3.1 m, Comperhesivif Meta-Analysis 3.3.070, and Review Manager Cochrane 5.4.1 for lunak and risk analysis. Results: The heterogeneity analysis of on- and centron residuals on IONV indicated I-squared (I2) of 99%, hypotension I2=98%, and pruritus I2=97% for 1103 people in thirteen studies. The Random Effect Model revealed a significant positive effect on Standard Mean Difference (SMD) analysis (IONV = 5.77, 95% CI: 0.58, 10.95; p=<0.01), decreased hypotension (SMD = -2.14, 95% CI: -4.80, 0.52= p=<0.01), and pruritus incidence (SMD = 0.67, 95%). CI = -1.48 to 2.83; p < 0.01. The meta regression subgroup revealed a significant decrease in IONV in the first 5 minutes with an Odds Ratio of 0.38 (95%-CI 0.04 to 3.62; p=<0.01) for the 4mg dose. Conclusions: While useful in controlling perioperative and hypotension, ondansentron may exacerbate pruritus. Ondansentron dose and pruritus effects need additional study.